Increasing of wear resistance of steels due to obtaining metastable structure, which can to strengthen by itself under the pressure - Малинов, Леонид Соломонович; Солидор, Наталья Аркадьевна; Харлашкин, Виктор Алексеевич; Аниченков, Виктор Васильевич (Eastern-European Journal of Enterprise Technologies, 2012)
The results of influence of different hit treatment on wear resistance of steels 55G, 65G and 75G are shown in this research paper. It is proved that due to efficient hit treatment it may be obtained good combination of service properties.